Legal aspects of sustainable development of seaports in Poland - Adamowicz Magdalena; Puszkarski Jakub (SHS Web of Conferences, 2018)
Sea ports are the driving force behind economic development. If ports operate efficiently and in conditions that support growth, the entire national economy gains. However, ports facing barriers and a scarcity of favourable factors have a negative impact on a country’s economy. In terms of sustainable development, it does not suffice to increase the economic potential of ports; it is also necessary to strive for balance between social and environmental interests, so that the sea may provide for everyone, including the future generations. It is important to enable ports to operate in such a way as not to stunt their competitiveness but to allow for development without disrupting the social and economic balance. The aim of this article is to investigate whether the existing legal instruments in the field of sustainable development of ports match the specific profile of ports as entities and whether the assumptions for sustainable development work well in practice. The article contains an analysis and assessment of legal regulations concerning sustainable development of sea ports. Selected legal instruments with direct or indirect impact on the formation of the sustainable development policy for Polish sea ports have been analysed at the global, European and national levels. Reference has been made to regulations related both to hard law and soft law. The article draws special attention to a balance between social, economic and environmental interests as a foundation for sustainable development.